Implementation of Kahoot! As A Learning Tool to Develop Mastery of Arabic Mufrodat for Class X Students at MA Al-Anwar Sarang - Iffat Maimunah; Habil Abyad; Arina Haque; Kristina Imron (ALSINATUNA, 2024)
Kahoot! Is a digital application that has great potential in its development as a learning media. Technological advances that go hand in hand with obstacles and challenges demand innovative learning media, especially in Arabic language learning. This study aims to explore the Kahoot! learning media as a game media to improve mufradat mastery in class X students of MA Al-Anwar Sarang and review student responses to its implementation. The method used in this study is experimental with descriptive qualitative techniques. Data collection methods use observation, interview, and questionnaire techniques. In analyzing the data, researchers used the effectiveness of learning media approaches as a benchmark for application assessment. The results of this study explain the strategies and steps of the Kahoot! learning media can be implemented innovatively through various products by utilizing the application's features. Student responses to the implementation of the Kahoot! game media are very positive and interactive, so learning is easy to understand, interesting, and creative to apply in the learning process at school. This application has also been proven to increase students' enthusiasm for learning. It acts as a quiz innovation that can improve the quality of student involvement in learning in the classroom. Developing technology-based learning media, such as Kahoot!, requires creativity in creating practical innovations for the teaching and learning process. Teachers are expected to be more creative in choosing learning media to improve students' mufradat memorization.